IN VIVO OBSERVATION OF RETINAL VASCULAR DEPOSITS USING ADAPTIVE OPTICS IMAGING IN FABRY DISEASE. Issue 8 (August 2020) - Sodi, Andrea; Germain, Dominique P.; Bacherini, Daniela; Finocchio, Lucia; Pacini, Bianca; Marziali, Elisa; Lenzetti, Chiara; Tanini, Ilaria; Koraichi, Fairouz; Coriat, Caroline; Nencini, Patrizia; Olivotto, Iacopo; et al.
Abstract : Purpose: To report a novel finding in patients with Fabry disease, that is, the observation by adaptive optics ophthalmoscopy of intracellular lipidic deposits in retinal vessels. Methods: Observational two-center case series. Eighteen patients with genetically proven Fabry disease underwent flood-illumination adaptive optics ophthalmoscopy imaging (rtx1; Imagine Eyes, Orsay, France) of retinal vessels. Results: Fourteen patients (78% of all patients; 7 of the 10 women and 7 of the 8 men) showed paravascular punctuate or linear opacities in both eyes. In the least-affected patients, these were seen only in the wall of precapillary arterioles as discrete spots of 5 µ m to 10 µ m large, whereas in those more severely affected, capillaries and first-order vessels were also involved with diffuse opacification of the wall. These deposits sometime showed a striated pattern, suggesting colocalization with vascular smooth muscle cells. Conclusion: Adaptive optics ophthalmoscopy of retinal vessels may be of interest for patients with Fabry disease, providing noninvasive, gradable evaluation of microvascular involvement. Abstract : Supplemental Digital Content is Available in the Text.Patients with Fabry disease underwent adaptive optics ophthalmoscopy of retinal vessels. Paravascular opacities corresponding to intracellular lipidic deposits were found in both eyes of most patients. We conclude that adaptive optics ophthalmoscopy provides noninvasive and gradable evaluation of microvascular involvement in Fabry disease.